Parent-reported indicators for detecting feeding and swallowing difficulties and undernutrition in preschool-aged children with cerebral palsy - Benfer, K.; Weir, K.; Ware, R.; Davies, P.; Arvedson, J.; Boyd, Roslyn; Bell, K. (Wiley-Blackwell Publishing Ltd., 2017)
© 2017 Mac Keith Press Aim: To determine the most accurate parent-reported indicators for detecting (1) feeding/swallowing difficulties and (2) undernutrition in preschool-aged children with cerebral palsy (CP). Method: This was a longitudinal, population-based study, involving 179 children with CP, aged 18 to 60 months (mean 34.1mo [SD 11.9] at entry, 111 males, 68 females [Gross Motor Function Classification System level I, 84; II, 23; III, 28; IV, 18; V, 26] , 423 data points). Feeding/swallowing difficulties were determined by the Dysphagia Disorders Survey and 16 signs suggestive of pharyngeal phase impairment. Undernutrition was indicated by height–weight and skinfold composite z-scores less than −2. Primary parent-reported indicators included mealtime duration, mealtime stress, concern about growth, and respiratory problems. Other indicators were derived from a parent feeding questionnaire, including ‘significant difficulty eating and drinking’. Data were analysed using multilevel mixed-effects regression and diagnostic statistics. Results: Primary parent-reported indicators associated with feeding/swallowing were ‘moderate–severe parent stress’ (odds ratio [OR]=3.2 [95% confidence interval CI 1.3–7.8] ; p < 0.01), ‘moderate–severe concern regarding growth’ (OR=4.5 [95% CI 1.7–11.9]; p < 0.01), and ‘any respiratory condition’ (OR=1.8 [95% CI 1.4–5.8]; p < 0.01). The indicator associated with undernutrition was ‘moderate–severe concern regarding growth’ (height–weight OR=13.5 [95% CI 3.0–61.3]; p < 0.01; skinfold OR=19.1 [95% CI 3.7–98.9]; p < 0.01). ‘Significant difficulty eating and drinking’ was most sensitive/specific for feeding outcome (sensitivity=58.6%, specificity=100.0%), and ‘parent concern regarding growth’ for undernutrition (sensitivity=77.8%, specificity=77.0%). Interpretation: Parent-reported indicators are feasible for detecting feeding and swallowing difficulties and undernutrition in children with CP, but need formal validation. What this paper adds: Parent-reported indicators can detect feeding/swallowing difficulties and undernutrition in children with cerebral palsy. Most accurate screening questions were 0–10 scales for ‘difficulty eating’ and ‘difficulty drinking’. Supplementation of these scales with additional indicators would improve detection.